Razones y riesgos del outsourcing de sistemas de información: Un análisis de su situación y evolución - M. R. González Ramírez; J. L. Gascó Gascó; Juan Llopis Taverner (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2010)
This study elaborates a proposal of the main reasons and risks at Information Systems Outsourcing. We try also to evaluate these reasons and risks in the case of the largest Spanish firms and to analyse their temporary evolution. To achieve this objective a questionnaire has been carried out among the Information Systems managers of the largest Spanish firms. Attending to the interviewed, outsourcing reasons are not based merely on the reduction of costs but in strategic reasons while the main risks relapse in the side of the supplier of the services.
Keywords: M12; O32; 330; information systems; information technologies; outsourcing; reasons; risks